2009
DOI: 10.1074/jbc.m109.038497
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for T Cell Alloreactivity among Three HLA-B14 and HLA-B27 Antigens

Abstract: The existence of cytotoxic T cells (CTL) cross-reacting with the human major histocompatibility antigens HLA-B14 and HLA-B27 suggests that their alloreactivity could be due to presentation of shared peptides in similar binding modes by these molecules. We therefore determined the crystal structures of the subtypes HLA-B*1402, HLA-B*2705, and HLA-B*2709 in complex with a proven self-ligand, pCatA (peptide with the sequence IRAAPPPLF derived from cathepsin A (residues 2-10)), and of HLA-B*1402 in complex with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…The fact that prolines apply significant torsional limitations on the peptide backbone makes them an obvious candidate for imposing selfconstraints. The clearest example to date of proline constraints in an MHC-I restricted peptide whose structure has been solved is the 9mer IRAAPPPLF derived from the signal sequence of cathepsin A (34). The frequency of prolines in immunogenic peptides is likely to reflect that certain MHC-I alleles, notably the HLA B7 supertype, exhibit specificity for a P2-Pro anchoring motif.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that prolines apply significant torsional limitations on the peptide backbone makes them an obvious candidate for imposing selfconstraints. The clearest example to date of proline constraints in an MHC-I restricted peptide whose structure has been solved is the 9mer IRAAPPPLF derived from the signal sequence of cathepsin A (34). The frequency of prolines in immunogenic peptides is likely to reflect that certain MHC-I alleles, notably the HLA B7 supertype, exhibit specificity for a P2-Pro anchoring motif.…”
Section: Discussionmentioning
confidence: 99%
“…In this procedure, the protein sequences of HLA alleles B*13:01, B*15:05 and B*39:01 were retrieved from the International Immunogenetics (IMGT)/HLA database [17] and their structures were modeled using MODELLER [18,19] from Protein Data Bank IDs 1N2R [20], 1XR8 [21] and 3BVN [22] with 100, 99 and 98% sequence identity, respectively. Then, we generated the structure of SASP using CORINA [23].…”
Section: In Silico Dockingmentioning
confidence: 99%
“…B*2705 and B*1403 show only 3%-5% peptide sharing 14 . Interestingly, a single peptide, IRAAPPPLF, derived from cathepsin A signal sequence residues 2-10, binds B*2705, B*2709, B*1402, and B*1403, and a crystallographic study of the first 3 alleles (B*1403 crystals could not be obtained) showed that all bind this peptide with the same conformation 15 . This peptide binding evidently might account for the very limited alloreactive cytotoxic T lymphocytes (CTL) cross-reactivity observed among B*2705, B*1402, and B*1403 14 .…”
Section: Biochemistry and Peptide Repertoires Of The B27 Subtypesmentioning
confidence: 99%